Effect Of Income And Price Changes On Rice Demand Elasticity - Kusumawardani, Niniek Dyah; Purwanti, Gettik Andri; Sofwani, Ahmad; Mondiana, Yani Quarta (SEAN Institute, 2024)
This study aims to analyze the influence of changes in income and prices on rice demand in Sidoarjo City. Rice is still the main staple food in the region, but economic and social dynamics can affect its consumption patterns. Using monthly time series data from January 2018 to December 2022, this study applies a multiple regression analysis method to estimate the elasticity of prices and income to rice demand. The results of the study show that rice prices have a negative and significant influence on demand. Meanwhile, per capita income has a positive and significant influence. The regression model has a determination coefficient (R²) of 0.564, indicating that 56.4% of the variation in rice demand can be explained by changes in price and income. This finding implies the importance of maintaining rice price stability and anticipating an increase in demand in line with economic growth. The study also highlights the potential for food diversification, given the relatively low elasticity of income to rice demand. The results of this study can be an input for policymakers in formulating food security and rice price control strategies in Sidoarjo City.